2022
DOI: 10.1515/med-2022-0436
|View full text |Cite
|
Sign up to set email alerts
|

Radiation increases COL1A1, COL3A1, and COL1A2 expression in breast cancer

Abstract: Background Radiotherapy-associated secondary cancer is an important issue for the treatment of breast cancer (BCa). This study aimed to investigate the molecular mechanism and genetic risk factors for radiation-associated secondary diseases in BCa. Methods The differentially expressed genes (DEGs) between preradiation and postradiation BCa samples in the GSE65505 dataset were obtained. The pathways related to the radiation-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Specifically, there were four genes, namely PDGFRL, UCHL1, COL5A2, and COL3A1 that were common among all three-DEGs from the EMAT gene signature, the Zurich and the Stavanger cohort. Interestingly, all these genes have been implicated in promoting invasion and metastasis and associated with poor survival outcomes in breast cancer patients [32][33][34]. Previous studies also found that the expression levels of COL3A1 were higher in primary TNBC tumors compared to lymph node metastasis [35].…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, there were four genes, namely PDGFRL, UCHL1, COL5A2, and COL3A1 that were common among all three-DEGs from the EMAT gene signature, the Zurich and the Stavanger cohort. Interestingly, all these genes have been implicated in promoting invasion and metastasis and associated with poor survival outcomes in breast cancer patients [32][33][34]. Previous studies also found that the expression levels of COL3A1 were higher in primary TNBC tumors compared to lymph node metastasis [35].…”
Section: Discussionmentioning
confidence: 97%
“…COL1A1 and COL6A3 have been shown to be signi cantly associated with overall survival and brain metastasis in breast cancer patients [20]. The study by Yao et al showed that COL1A1 and COL1A2 in breast cancer tissues were up-regulated by radiotherapy, and it might lead radiation-associated secondary non-breast diseases [21].…”
Section: Discussionmentioning
confidence: 99%
“…COL1A1 and COL6A3 have been shown to be significantly associated with overall survival and brain metastasis in breast cancer patients [20]. The study by Yao et al showed that COL1A1 and COL1A2 in breast cancer tissues were up-regulated by radiotherapy, and it might lead radiation-associated secondary non-breast diseases [21].…”
Section: Discussionmentioning
confidence: 99%